2018
DOI: 10.4067/s0718-07642018000500267
|View full text |Cite
|
Sign up to set email alerts
|

Cultura Innovadora en Empresas Contratistas de las Minas de Explotación de Carbón en Colombia

Abstract: El artículo analiza los rasgos y los tipos de cultura innovadora en contratistas de empresas mineras del Departamento del Cesar en Colombia. La investigación es cuantitativa y descriptiva. Los resultados indican que el rasgo predominante en las características de la organización dominante, es la concepción de la empresa como una familia extensa. Frente a la gestión de personal, predomina el fomento del trabajo en equipo, el consenso y la participación. Asimismo, el rasgo predominante del vínculo organizacional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Naranjo & Calderón (2015) analyzed the links between corporate culture, innovation, and performance in Spanish firms, where it was found that organizational culture can foster innovation and performance or be a barrier for them based on the company's values. Unlike Aroca et al (2018) and Alvarado & Pumisacho (2015), an adhocratic culture best predicted innovation and performance. Limas (2020) found that Colombian business managers point out that innovation is fundamental for sustainability and strengthening business.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Naranjo & Calderón (2015) analyzed the links between corporate culture, innovation, and performance in Spanish firms, where it was found that organizational culture can foster innovation and performance or be a barrier for them based on the company's values. Unlike Aroca et al (2018) and Alvarado & Pumisacho (2015), an adhocratic culture best predicted innovation and performance. Limas (2020) found that Colombian business managers point out that innovation is fundamental for sustainability and strengthening business.…”
Section: Methodsmentioning
confidence: 95%
“…Marulanda et al (2016) analyzed the organizational culture in small and medium-sized companies in Colombia, where they found that a critical factor for a company's innovation is knowledge management applied in companies. In the mining sector, Aroca et al (2018) found that the organizational culture allows workers to be in a familiar environment to encourage innovation. Acosta et al (2020) found in a given Colombian company that a corporate culture based on leadership rather than strict hierarchy allows employees to express their ideas with more confidence, which allows them to have a learning-oriented organizational climate.…”
Section: Methodsmentioning
confidence: 99%
“…This can be explained through concepts such as organizational culture, which is defined by Olga Lucia Anzola (in Mendoza and Ortiz, 2006) as "a set of social practices, material and immaterial, that account for the characteristics that distinguish a community since they establish a common affective atmosphere and a shared cognitive framework". Also, as stated by Aroca et al, (2018) in terms of a set of values, norms, and behaviors of the members of an organization.…”
Section: Leadershipmentioning
confidence: 99%